Smart Materials fabricated by powder metallurgy: a review / Nur Adryna Farhana Norizam - Norizam, Nur Adryna Farhana (2022)
Smart Materials (SM) are innovative materials with several applications, including the aerospace sector, biomedicine, and others. Shape memory alloys (SMA), piezoelectric materials, magnetostrictive materials, and electrostrictive materials are some of the categories. Powder metallurgy (PM) is the study of metal powder processing, which involves the synthesis, characterization, and conversion of metal powder into usable engineering components. The benefits of the PM technique include the ability to create unique designs that are difficult to construct using standard techniques, as well as the economic and distinctive characteristics of PM to generate multipart products, which make SM fabricated by PM increasingly appealing for substituting wrought materials. Several studies on SM and PM have been conducted; nevertheless, there are far too many powder metallurgical approaches for producing SM. As a result, researchers are unable to determine which strategy is optimal for increasing the characteristics of SM using PM, hence development is slow. The purpose of this study is to examine the evidence for a relationship between SM and PM. Based on the results, shape memory polymers (SMPs) are the best form of SMAs since they have great strain recovery, low density, cheap cost, simple manufacture, biocompatibility, biodegradability, mouldability, and lightweight. Furthermore, due to its lead-free perovskite, high dielectric permittivity, and good piezoelectric coefficient, BaTiO3 is regarded as the best piezoelectric material. Direct Ink Writing and Spark Plasma Sintering are the ideal production technologies for SMPs and BaTiO3, respectively. This research will be valuable to academics seeking the best PM techniques for SMPs and BaTiO3. The present trends in SMP and BaTiO3 production were the primary focus of this review. In the future, this study should provide more detailed information on advanced PM approaches, notably DIW and SPS.